PENGARUH TATA KELOLA PERUSAHAAN, STRUKTUR MODAL, DAN INVESTASI MODAL TERHADAP NILAI PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI VARIABEL MODERASI (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2021-2024) - Fiki Sabila Firdaus; Abdul Rohman (Diponegoro Journal of Accounting, 2026)
This study aims to examine the effect of corporate governance proxied by blockholder ownership, capital structure proxied by the debt-to-equity ratio (DER), and capital expenditure on firm value proxied by price-to-book value (PBV), with profitability measured by return on assets (ROA) serving as a moderating variable. The research sample consists of manufacturing companies listed on the Indonesia Stock Exchange during the 2021–2024 period. This study employs a quantitative approach using panel data regression and moderated regression analysis (MRA) with EViews 12. The findings indicate that blockholder ownership has a positive and significant effect on firm value, whereas DER has a negative and significant effect on firm value. Meanwhile, capital expenditure does not have a significant effect on firm value. Furthermore, ROA strengthens the relationship between blockholder ownership and firm value but does not moderate the relationship between DER and firm value or between capital expenditure and firm value.